Merit-Based Civil Service Management: A Rule of Law Perspective - Fitriyanti Rahman; Fence M. Wantu; Zamroni Abdussamad (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study examines the optimization of merit-based civil service management within the framework of the rule of law, focusing on the gap between normative legal provisions and bureaucratic practices in Indonesia. Despite bureaucratic reform mandates since the 1998 Reform Movement, civil service governance continues to face challenges such as inefficiency, weak accountability, and patronage culture. This research aims to analyze the effectiveness of the merit system as a legal instrument to promote professionalism, neutrality, and accountability within the Civil Service (Aparatur Sipil Negara/ASN), particularly following the enactment of Law Number 20 of 2023, which abolished the Civil Service Commission (KASN). Employing a normative juridical method with a descriptive-analytical approach, this study reviews statutory regulations, academic literature, and official reports from KASN and the National Civil Service Agency (BKN). The findings indicate that although the merit system is legally grounded in Law Number 5 of 2014 and Law Number 20 of 2023, its implementation remains inconsistent due to weak oversight mechanisms, limited regulatory clarity, and uneven digital infrastructure readiness. The elimination of independent supervision has reduced checks and balances, while disparities in the adoption of ASN digital systems hinder transparency. This study proposes strengthening derivative regulations, reconstructing independent oversight through a merit audit mechanism, and accelerating digital transformation. The study contributes by integrating administrative law, meritocracy, and good governance principles to position the merit system as a legal and managerial tool for building a professional and accountable bureaucracy.